Short sleeping duration is associated with a higher risk of asymmetric handgrip strength among older Chinese males: a cross-sectional study evidence from the China health and retirement longitudinal study - Wang, Yilin; Li, Mei; Chen, Xiaoyan (Frontiers in Public Health, 2023)
Objective: This study aimed to explore the potential correlation between sleeping duration and the risk of handgrip strength (HGS) asymmetry in older Chinese adults. Methods: The data of participants (65+ years of age) were obtained from the first Wave 1 (2011) of the China Health and Retirement Longitudinal Study (CHARLS). Information on sleeping duration during the previous month was collected from self-reports and was divided into three groups: long (＞8 hours), normal (6-8 hours), and short (＜ 6 hours). HGS was computed as the average of two tests per hand and asymmetric HGS was diagnosed when the ratio of average non-dominant to average dominant HGS was greater than 1.1 or less than 0.9. Logistic regression analyses were employed to gauge the relationship between sleeping duration and asymmetric HGS risk. Results: In total, 3,174 participants were enrolled in this analysis, of whom 51.54% (1,636/3,174) were male. The proportions of asymmetric HGS were 42.18% in males and 41.87% in females. The sleeping duration (hours) in the asymmetric and non-asymmetric HGS groups were 6 h (5,8) and 7 h (5,8) in males with a significant difference between them (p=0.015), and 6 h (5,8) and 6 h (5,8) in females with no significant difference (p=0.415). Compared with non-asymmetric HGS individuals, the proportions of normal, short, and long sleeping duration were 40.4%, 47.3%, and 37.7% in males with a significant difference (p=0.023), and 42.4%, 40.3%, and 43.8% in females with no significant differences (p=0.685). An adjusted logistic regression analysis model confirmed that short sleeping duration was significantly associated with asymmetric HGS risk among older males (p=0.048, OR=1.252, 95%CI:1.002-1.565). Conclusions: The results demonstrated that short sleeping duration (＜6 h) was a risk factor for increased HGS asymmetry among older Chinese males.